Direct Selling: From Door To Door To E-Commerce - Alturas, Bráulio (2009)
Direct selling is exhibiting substantial growth in sales revenues and number of salespeople involved. Also the acceptation of consumers is growing. During the last decade direct selling organizations (DSOs) are using the Internet more and more, either to communicate with the salespersons, either to promote the products and the business to the consumers. This research is aiming to contribute to a better understanding of how DSOs are using the Internet, for that we have interview 11 managers of DSOs operating in Portugal. Results show that DSOs use the Internet as a support to their main business. We then discuss aspects of importance for further extensions.